PROSEDUR PEMBAYARAN PBJT JASA PERHOTELAN SAAT TERJADI GANGGUAN SISTEM PEMBAYARAN DI BANK 9 JAMBI PADA BPPRD KOTA JAMBI - Maharani , Kurniaty; Heriyani, Heriyani (Jurusan Akuntansi FEB Universitas Jambi, 2026)
This study aims to determine the payment procedures for Certain Goods and Services Tax (PBJT) for Hotel Services during a payment system disruption at Bank 9 Jambi at the Jambi City Regional Tax and Retribution Management Agency (BPPRD). The writing method in this report uses a descriptive qualitative method through interviews and literature studies. The disruption of the payment system in February 2026 caused the validation and settlement process, which was previously carried out automatically by Bank 9 Jambi, to shift to the responsibility of the revenue treasurer of the Jambi City BPPRD through the Integrated Tax and Retribution Information System (SIMPATTI). The smoothness of the payment system has a significant influence on the effectiveness of tax services, so that the process can run effectively. The implications of this study emphasize the importance of establishing emergency regulations based on multi-channel Standard Operating Procedures (SOPs) and increasing the reliability of the mitigation system (disaster recovery plan) to minimize the risk of a decrease in Regional Original Income (PAD).